2000
DOI: 10.1111/j.8755-8920.2000.440301.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Paternal Mononuclear Cells’ Immunization a Successful Treatment for Recurrent Spontaneous Abortion?

Abstract: These results indicate that alloimmunization may be useful in the treatment of RSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
1
24
0
3
Order By: Relevance
“…The data of immunotherapy during early pregnancy should be analyzed in the light of the number of previous miscarriage and gestational window. Most of the controversial studies performed immunotherapy only once or twice before pregnancy [50,55], whereas in most of the successful studies, PL immunization was performed either at the regular interval of 3 -6 weeks before pregnancy [31,45] or once before, following the course of immunization, and a few more immunizations during pregnancy [56]. Various risk and side effects (twin pregnancies, preterm delivery, growth retardation, neonatal thrombocytopenia and certain congenital abnormalities) have been reported to be involved in PL-immunized women with RSA [49,55,57 -61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of immunotherapy during early pregnancy should be analyzed in the light of the number of previous miscarriage and gestational window. Most of the controversial studies performed immunotherapy only once or twice before pregnancy [50,55], whereas in most of the successful studies, PL immunization was performed either at the regular interval of 3 -6 weeks before pregnancy [31,45] or once before, following the course of immunization, and a few more immunizations during pregnancy [56]. Various risk and side effects (twin pregnancies, preterm delivery, growth retardation, neonatal thrombocytopenia and certain congenital abnormalities) have been reported to be involved in PL-immunized women with RSA [49,55,57 -61].…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences which revealed that immunological recognition of pregnancy is important for the maintenance of gestation, and inadequate recognition of fetal antigens might lead to abortion in women with RSA [30,31]. Alloimmunity has been indicated in several studies by showing an association of habitual abortion with an increased sharing of human leukocyte antigens (HLA) with the father that may prohibit the production of antipaternal cytotoxic antibodies (APCA), anti-idiotypic antibodies (Ab2) and mixed lymphocyte reaction blocking antibodies (MLR-Bf) in the mother.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of the immunotherapy has been controversial [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], but a meta-analysis concerning the immunotherapy for patients with URA reported by the Recurrent Miscarriage Immunotherapy Trialists Group in 1994 [13], Clark in 2008 [7] and 2012 [14] concluded and Liu et al in 2016 [25] concluded that the immunotherapy may be highly effective. In addition, Pandey et al reported a significant improvement in pregnancy outcome in the patient group in their double-blind randomized trial of husband's lymphocyte immunization for women with recurrent spontaneous abortion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy for these patients using their husbands' or a third party's leukocytes has been reported [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Although the efficacy of this modality has been controversial, an analysis of controlled clinical trials revealed the efficacy for patients with Unexplained Recurrent Abortion (URA) [7,14,19,26,27], especially for those who were negative for blocking antibodies evaluated by a mixed lymphocyte culture reaction between spouses (MLR-BAbs) [19,22,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This varied from autologous blood injections to vaginal placebo pessaries to saline injections. In one study, patients used expectant management (68). The number of included couples was 261 and varied from 19 to 85.…”
mentioning
confidence: 99%